Evaluation of the efficacy of bromfenac sodium in the treatment of dry eye disease - I.A. Loskutov; E.F. Semashko; E.N. Khomyakova; E.I. Makukha; N.E. Kostina (РМЖ "Клиническая офтальмология")
I.A. Loskutov, E.F. Semashko, E.N. Khomyakova, E.I. Makukha, N.E. Kostina M.F. Vladimirskiy Moscow Regional Research and Clinical Institute, Moscow, Russian Federation Background: to date, the efficacy of anti-inflammatory treatment in dry eye disease (DED) is still relevant. Aim: to evaluate the efficacy and safety of bromfenac sodium 0.09% ophthalmic solution plus artificial tears in patients with DED. Patients and Methods: 175 patients (350 eyes) with DED receiving artificial tears were enrolled. Subjective and objective assessment of symptom severity was performed and DED stage was determined before and 4 weeks after treatment with bromfenac sodium 0.09% ophthalmic solution based on the results of the Ocular Surface Disease Index (OSDI) questionnaire, Schirmer's test and Norn's test. Adverse events were registered to assess the safety of bromfenac sodium 0.09%. Results: complex treatment of DED resulted in a 1.4-fold increase in Schirmer's test and Norn's test score and a significant improvement in typical symptoms based on the OSDI score. The average OSDI score decreased by 56% compared to baseline. The number of patients with moderate to severe DED decreased by 7% and 55% respectively. The number of patients with mild DED increased by 21%. After 4 weeks of treatment, 41% of patients were symptom free. All changes during the study were significant (p<0.05). No adverse events were reported with the use of bromfenac sodium 0.09%. Conclusion: bromfenac sodium 0.09% ophthalmic solution is clinically effective in DED. This medication increases total tear production, reduces the severity of symptoms and decreases the number of patients with severe and moderate disease, thereby improving the quality of life of these patients. Keywords: bromfenac sodium, OSDI, dry eye disease, Schirmer's test, treatment efficacy. For citation: Loskutov I.A., Semashko E.F., Khomyakova E.N., Makukha E.I., Kostina N.E. Evaluation of the efficacy of bromfenac sodium in the treatment of dry eye disease. Russian Journal of Clinical Ophthalmology. 2024;24(1):7–13 (in Russ.). DOI: 10.32364/2311-7729-2024-24-1-2.